Succession of a natural desert vegetation community after long-term fencing at the edge of a desert oasis in northwest China - Zhang, Yan; Wang, Guohua; Gou, Qianqian; Zhang, Yu; Liu, Jing; Gao, Min (Frontiers in Plant Science, 2023)
In this study, we selected a typical degraded desert plant community (Reaumuria soongorica–Nitraria tangutorum community) on the edge of a desert oasis in northwestern China as the research object, and investigated succession in this plant community and the corresponding changes in soil physical and chemical characteristics over 10 years of fencing to analyze their mutual feedback mechanisms. The results showed that: 1) The diversity of plant species increased significantly in the community, and the species in the herb layer increased from 4 in the early stage to 7 in the late stage; community dominant species also changed: the dominant species of the shrub layer shifted from N. sphaerocarpa in the early stage to R. songarica in the late stage; the herbaceous layer changed from the annual herb Suaeda glauca in the early stage to S. glauca and Artemisia scoparia in the middle stage, and ultimately to A. scoparia and Halogeton arachnoideus in the late stage. In the late stage, Zygophyllum mucronatum, H. arachnoideus and Eragrostis minor began to invade, and the density of perennial herbs also increased significantly . 2) With the progression of years fenced, the contents of soil organic matter and total nitrogen first decreased and then increased, while the contents of available nitrogen, available potassium, and available phosphorus showed the opposite trend. 3) The changes in community diversity were mainly affected by the nursing effects of the shrub layer, and soil physical and chemical properties. The vegetation density of shrub layer significantly increased with the increase of fencing years, and the nursing effect of the shrub layer promoted the growth of the herbaceous layer. On the other hand, shrub layer diversity was positively correlated with deep soil water content, and the diversity of the herbaceous layer was positively correlated with soil organic matter, total nitrogen, and soil pH. The density of the dominant shrub species was restored and the species diversity was significantly increased, especially in the herb layer. Studying the community succession and soil environmental factors under long-term fencing holds great significance for understanding community vegetation restoration and ecological reconstruction at the edge of desert oases.